School leadership development in Saudi Arabia: policy-makers’ and participants’ perspectives - Alziyadi, Zayed (2025)
This thesis examines school leadership development in Najran, Saudi Arabia by conducting 35 interviews with principals, junior teachers, senior teachers and policy-makers. The study reveals mixed perceptions regarding the effectiveness of leadership development programmes conducted by the Ministry of Education. Policymakers claim that the Ministry is actively working on initiatives to enhance leadership capabilities through developing soft skills and fostering collaboration. Exchange programmes are utilised to facilitate collaboration and networking among teachers, although many of these events are perceived to lack a validated methodology for promoting leadership skills. The Tatweer programme offers some leadership development opportunities, but participation varies significantly across schools. Some schools developed their own successful leadership initiatives, while others lack sufficient support. Self-development emerged as a crucial factor for leadership development, particularly in schools with fewer formal opportunities. Overall, the study suggests that, while Ministry-led programmes are valuable, they need substantial improvement to address the leadership development needs of both junior and senior teachers.